G228 Understanding the experience of young people undergoing maintenance haemodialysis therapy in an adult unit. (May 2019) - Gafton, J; Murphy, L; Fletcher, N; Hothi, D; Cove-Smith, A
Abstract : Aim: To understand the experience of young adults on haemodialysis, and utilise their unique perspectives in the development of young person-centred haemodialysis services. Background: Children, adolescents and young adults constitute <5% of patients with end-stage renal failure (1). The fraction of these who attend dialysis units are a significant minority even among their peers, as 73% of 18–24 year olds on RRT in the UK have a functioning transplant (2).These patients have been found to experience a strong sense of 'difference' in terms of body image and ability to participate in activities compared to peers; 'thwarted or moderated dreams and ambitions'; and 'uncertainty and liminality' (3). NICE guidelines on transition, advocate for the 'co-production' of 'person-centred' transition services to build independence (4). A 2010 BAPN/RA report discussed the value of Young Adult Renal Units, offering outpatient services (5). Our project explores young adults' views experience of dialysis and their ideas for an individualised service. Methods: We conducted semi structured interviews with 9 dialysis patients (5 male, 4 female) aged 19–24 years, who were under the care of Barts Health NHS Trust and had been on haemodialysis for at least 6 months. We used a narrative analysis approach, interpreting responses using the experience of care model. 8 out of 9 gave consent for audio recording, allowing for two researchers to establish concordance for each. Results: A number of common themes emerged in our discussions. 7/9 participants mentioned the negative impact of being surrounded by significantly older patients, 7/9 highlighted a lack of access to internet and entertainment and 8/9 described the impact dialysis had on future prospects. 8/9 wanted a dedicated young adult unit, with integration of flexible dialysis times, peer mentors and education resources all ranked of high importance. Conclusion: There was strong support for a dedicated young adult unit among this cohort of patients, who felt it would improve their experience on dialysis, and have a positive impact on their health and wellbeing. Ensuring smooth transition between services and adequate clinical support will be key considerations in its design.